Школа юных скаутов. Как найти клад: повести / Эдуард Веркин - Веркин Эдуард Николаевич (Серия "Только для мальчишек", 2005)
Экземпляры: (20181010) / Инвентарный номер: 30675 / Цена: 49.90 / Сис.шифр: Р2 / Авт.знак: В31 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6